Pemilihan Pusat Pertumbuhan Baru pada Daerah Mitra Ibu Kota Nusantara: Studi Kasus Kecamatan Penajam - Miswar Ariansyah; Jordan, Nadia Almira; Hidayat, Arief; Pratomo, Rahmat Aris (Journal of Infrastructure Policy and Management (JIPM), 2024)
The relocation of Indonesia’s Capital City of Nusantara (IKN) represents the government’s strategy to reduce regional disparities in the country. Penajam Subdistrict, which directly borders IKN area and serves as one of its partner areas, has significant potential as an economic driver, particularly for food security. Its geographical location gives it agricultural advantages, especially in the plantation subsector, which supports the national agricultural activities as directed by Presidential Regulation No. 63 of 2022. This potential may encourage the establishment of new growth centers that drive the economic sector through their leading plantation commodities. The development of these centers may also generate optimal polarization and downward trickling effects that benefit IKN partner areas. This study aims to identify new growth centers at a micro level in Penajam Subdistrict to support spatial utilization that aligns with IKN needs and sustainable regional development. Employing a quantitative method, this research utilizes centrality and accessibility index analysis as well as Location Quotient (LQ) techniques. The results of the study show that eight villages in Penajam have the potential to become new growth centers and serve as partner areas to IKN.